Membrane-disruptive peptides/peptidomimetics-based therapeutics: Promising systems to combat bacteria and cancer in the drug-resistant era - Liming Lin; Jiaying Chi; Yilang Yan; Rui Luo; Xiaoqian Feng; Yuwei Zheng; Dongyi Xian; Xin Li; Guilan Quan; Daojun Liu; Chuanbin Wu; Chao Lu; et al. (Elsevier, 2021)
Membrane-disruptive peptides/peptidomimetics (MDPs) are antimicrobials or anticarcinogens that present a general killing mechanism through the physical disruption of cell membranes, in contrast to conventional chemotherapeutic drugs, which act on precise targets such as DNA or specific enzymes. Owing to their rapid action, broad-spectrum activity, and mechanisms of action that potentially hinder the development of resistance, MDPs have been increasingly considered as future therapeutics in the drug-resistant era. Recently, growing experimental evidence has demonstrated that MDPs can also be utilized as adjuvants to enhance the therapeutic effects of other agents. In this review, we evaluate the literature around the broad-spectrum antimicrobial properties and anticancer activity of MDPs, and summarize the current development and mechanisms of MDPs alone or in combination with other agents. Notably, this review highlights recent advances in the design of various MDP-based drug delivery systems that can improve the therapeutic effect of MDPs, minimize side effects, and promote the co-delivery of multiple chemotherapeutics, for more efficient antimicrobial and anticancer therapy.